Multi-responsive magnetic microsphere of poly(N-isopropylacrylamide)/carboxymethylchitosan hydrogel for drug controlled release. (20th October 2016) - Rodkate, Nantharak; Rutnakornpituk, Metha
Highlights: Multi-responsive carboxymethylchitosan (CMC) microspheres were synthesized in one step. They contained thermo-responsive poly(NIPAAm), pH-responsive CMC and magnetic nanoparticles. Spherical microspheres (30.0 ± 1.0 μm) were obtained by fine adjusting the condition formulations. The responsive properties were used for triggering/accelerating the releases of entrapped drugs. These results indicated their great potentials for uses in controlled release applications. Abstract: Multi-responsive composite microspheres were synthesized via an in situ free radical polymerization of thermo-responsive poly( N -isopropylacrylamide) (poly(NIPAAm)) in the presence of carboxymethylchitosan (CMC) and magnetite nanoparticles (MNPs) followed by glutaraldehyde crosslinking. Formulation conditions of the composite microspheres were tuned such that spherical microspheres with narrow size distributions were obtained (30.0 ± 1.0 μm in diameter). They responded well to an applied magnetic field and showed water swelling responses to the change in solution pH and temperature. The release of an entrapped indomethacin model drug was accelerated when the solution temperature was above its lower critical solution temperature (LCST) (50 °C) or when the solution pH was in basic conditions (pH 11). These responsive properties can be used as triggering mechanisms for releases of the entrapped drugs from the microspheres, indicating their great potentials for use in controlled release applications.